PAH residues and toxicity levels two years after an extensive oil spill on the northeast Brazilian coast - Choueri, Rodrigo Brasil; de Souza Abessa, Denis Moledo [UNESP]; de Carvalho, Maysa Ueda [UNESP]; Pazini, Bianca; Zanardi-Lamardo, Eliete; Rojas, Lino Angel Valcárcel; de Carvalho, Paulo Sérgio Martins; de Andrade, Nycolle Virgínia Maux; de Souza Santos, Lília Pereira; Ferraz, Mariana Aliceda; Alves, Aline Vecchio; Castro, Ítalo Braga (Elsevier, 2024)
The most extensive oil spill ever recorded in tropical oceans occurred between August 2019 and March 2020, affecting approximately 3000 km of the Brazilian coast. This study assessed the chemical contamination and toxicity of sediments collected from affected reef areas during two sampling surveys conducted 17 and 24 months after the peak of oil slick inputs. Our results indicated that neither PAH levels nor measured toxicity showed a significant contribution from the spilled oil, with concentrations and biological effects indistinguishable from those in unaffected areas. Similarly, no differences were observed between seasons. Furthermore, there was no discernible relationship between sediment toxicity results and the measured PAH concentrations. Therefore, while biological responses indicated toxicity in most assessed areas, these responses are likely related to other local sources. This evidence suggests a natural oil attenuation process contributing to local environmental recovery. Nonetheless, further investigation is needed for other areas affected by oil spills.
Keywords: Ecotoxicology; Pollution; Polycyclic aromatic hydrocarbon; Seawater; Sediments